Corporate governance and the expansion of the democratic franchise: beyond cross-country regressions. Issue 2 (3rd May 2016) - Lamoreaux, Naomi R.
ABSTRACT: This article documents the stark differences in the legal regulation of corporations in the United States compared to Britain and other Western European countries in the nineteenth century. The lack of alternative ways of obtaining 'corporate' advantages in common-law countries made the corporate form much more politically fraught than in civil-law countries. In the United States, general incorporation laws came after the attainment of universal white manhood suffrage and were part of a broader egalitarian movement to ensure that elites did not have advantages over everyone else. As a result, they were highly prescriptive, limiting corporations' size and duration and also mandating specific governance rules. In Great Britain, by contrast, general incorporation laws were passed in a context where only a small fraction of the population could vote. Because the interests at stake in the legislation were those of the business and financial elite, British company law (like the less politically controversial statutes enacted on the European continent) left the rules governing corporations largely to the contracting parties themselves. This paper also argues that understanding the patterns in general incorporation laws requires scholars to move beyond cross-country regressions to study the political economic processes that unfolded in these different settings.